Konstitutionalitas Undang-Undang No 16 Tahun 2017 Tentang Penetapan Perppu Nomor 2 Tahun 2017 Tentang Organisasi Masyarakat Ditinjau Dari UUD 1945 Dan Konsep Negara Hukum (Rechstaat) - Kurniawan, M. Beni (UI Scholars Hub, 2018)
This research is a normative study that is perscriptive in order to provide solutions to the problems of Civil Society Organizations in Indonesia. This paper study theConstitutionality of Article 61 and 62 of Act Number 16 of 2017 on Stipulating Government Regulation In Lieu of Law No. 2 of 2017 which regulates the Dissolution of CSOs if reviewed from the 1945 Constitution and the Rule of Law’s Concept. As a result of the research can be concluded that Article 61 and 62 of Act Number 16 of 2017 On Stipulating Perppu No. 2 of 2017 which gives authority to the government to dissolve CSOs unilaterally is Inconstitutional because Contrary to Article 1 paragraph 3 of Indonesia as a State of Law and Article 28 E paragraph 3 concerning freedom of association. And also there needs to be a revision of Government Regulation In Lieu of Law No. 2 of 2017 with still giving authority to the Judicial Boards (MA or MK) in deciding the dissolution of CSOs. It is also necessary to limit the time to the Judicial Boards in deciding cases of the dissolution of CSOs, to avoid an uncertain case and an inefficient time